Makna Tradisi Adat Barodak Sumbawa Tahun 1999-2002: Penelitian - Sukarddin, Sukarddin; Gustianingsih, Lala (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The purpose of this study is to find out more about the meaning of the Barodak tradition which is one of the traditions that still exists today, along with the development of the times this tradition has experienced a few changes in its implementation process. This study uses a historical research method with a qualitative descriptive approach, namely research that studies events or incidents in the past. The results of this study can find out about the process of implementing the Barodak tradition of Sumbawa traditional weddings. This Barodak tradition is part of the procession of the two prospective brides and grooms using traditional herbs and reddening the nails of the two prospective brides and grooms. In the procession of implementing this Barodak tradition there are 3 stages, namely: (1) Preparation of odak ingredients, (2) bridal bath, (3) odak process (scrub). The philosophy of this Barodak tradition is as follows: where the word odak symbolizes sincerity, unity of heart and determination, while Barodak rapancar itself means as a form of self-cleansing in order to carry out a sacred promise or, while for rapancar it gives a bright light so that it gives a touch of joy. The social values ​​contained in the Sumbawa barodak tradition are as follows: (1) The value of mutual cooperation, (2) The value of helping each other, (3) The value of family, (4) The value of caring, (5) The value of respect.